From Parental Support to Concrete Action: The Influence of Parent-Child Career Goal Congruence and Proactive Behavior on Students’ Career Engagement - Fitri Amalia; Arini Widyowati (Universitas Katolik Soegijapranata, 2026)
Career engagement refers to an individual’s involvement in their career development activities and is closely associated with career satisfaction and commitment to a chosen profession. External factors, such as parent-child career goal congruence, and internal factors, such as proactive career behavior, are considered important determinants of career engagement. This study aimed to examine the relationship between parent-child career goal congruence, proactive career behavior, and career engagement among university students. Using a quantitative survey approach, the study involved 237 psychology students aged 18-21 years from a university in Yogyakarta. Data were collected using the Career Engagement Scale, the Parent-Child Career Goal Congruence Scale, and the Proactive Career Behaviour Scale. Multiple linear regression analysis revealed a significant relationship among parent-child career goal congruence, proactive career behavior, and career engagement (p 0.001). The two independent variables jointly contributed 18.1% of the variance in career engagement. The findings indicate that students whose career goals are highly congruent with their parents' and who demonstrate proactive career behavior tend to be more actively engaged in their career development. These results have important implications for parents, higher education institutions, and career counselors in supporting students’ career engagement and facilitating the achievement of their professional goals.